Demographic Transition of the Bundelkhand Region: Understanding the Demographic Transition in Bundelkhand Region, Uttar Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The twentieth century witnessed an unprecedented rapid improvement in health care technologies and access to health care all over the world as a result there was a steep fall in the mortality and steep increase in longevity. The population realized these changes and took steps to reduce their fertility but the decline in fertility was not so steep. As a result the global population has undergone a fourfold increase in a hundred years and has reached in billions. This study will enlighten the population growth in Bundelkhand, Uttar Pradesh. As a result of these changes population growth ceases and population stabilizes. Experience in some of the developed countries suggest that in some societies even after attainment of stable population there may be a further decline in fertility so that there is a further reduction in the population- so called negative population growth phase of the demographic transition.